Tinjauan Yuridis Penggunaan Aplikasi Corel Draw X4 Ilegal Dalam Bisnis Desain Grafis Berdasarkan Undang - Undang Nomor 13 Tahun 2016 Tentang Hak Paten - Mala, Nurlaili Ika; Tioma R. Hariandja, SH., MH; Firda Laily Mufid, SH.,MH; Hoiru Nail, Muhammad (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2024)
Advances in digital technology have had a significant impact onIntellectual Property Rights (IPR), especially in the field of graphicdesign utilizing applications such as Corel Draw X4. Althoughthese applications are very popular and provide great economicbenefits, their illegal use has a negative impact on patent rights anddeveloper innovation. This research aims to examine the legalimplications of the illegal use of Corel Draw X4 in the graphicdesign business in Indonesia based on Law Number 13 Year 2016on Patent Rights. The method used is normative juridical, withstatutory and conceptual approaches. The results show that theillegal use of this software violates the exclusive rights granted tothe patent holder and is potentially subject to legal sanctions suchas fines or imprisonment. Corel Corporation has a mechanism todetect illegal use and offer alternatives to legal use, such as trialversions. Therefore, graphic designers and businesses are advised tocomply with patent rules to avoid adverse legal consequences andsupport the sustainable growth of the industry. Resolving disputesrelated to patent infringement can be done through litigation ornon-litigation approaches, with mediation as a more effective andefficient option.